Impeachment as a Means of Presidential Removal in the Study of Indonesian Constitutional Law Post-Reform - Ridwan Ridwan (Journal of Law and Humanities Review, 2025)
This article explores the implementation of criminal sanctions against the President of Indonesia for constitutional violations, focusing on the interplay of executive power and oversight mechanisms. It emphasizes the importance of understanding the limitations of law enforcement agencies and the necessity of preventive measures to avert such violations, aiming to maintain constitutional integrity and stability. The study critically examines the impeachment process as outlined in Articles 7A and 7B of the 1945 Constitution, highlighting its classification as a political decision and the roles of key institutions such as the MPR (People's Consultative Assembly), DPR (House of Representatives), and MK (Constitutional Court). The findings reveal that the impeachment mechanism, while necessary for upholding the rule of law, faces challenges including politicization and inefficacy in resolving political conflicts, which may lead to societal polarization. The article calls for a thorough evaluation of the impeachment process to identify weaknesses and enhance transparency, fairness, and community participation. Ultimately, it argues that a well-functioning impeachment mechanism is crucial for preserving democracy, maintaining the integrity of state institutions, and ensuring justice within the Indonesian political system.